Risk response towards roads is consistent across multiple species in a temperate forest ecosystem ... - Bastianelli, Matteo Luca; von Hoermann, Christian; Kirchner, Katrin; Signer, Johannes; Dupke, Claudia; Henrich, Maik; Wielgus, Elodie; Fiderer, Christian; Belotti, Elisa; Bufka, Luděk; Ciuti, Simone; Dormann, Carsten F.; et al. (Zenodo, 2024)
Roads can have diverse impacts on wildlife species, and while some species may adapt effectively, others may not. Studying multiple species' responses to the same infrastructure in a given area can help understand this variation and reveal the effects of disturbance on the ecology of wildlife communities. This study investigates the behavioural responses of four species with distinctive ecological and behavioural traits to roads in the protected Bohemian Forest Ecosystem in Central Europe: European roe deer (Capreolus capreolus), a solitary herbivore; red deer (Cervus elaphus) a gregarious herbivore; wild boar (Sus scrofa), a gregarious omnivore and Eurasian lynx (Lynx lynx), a solitary large carnivore. We used GPS data gathered from each species to study movement behaviour and habitat selection in relation to roads using an integrated step selection analysis. For all species and sexes, we predicted increased movement rates in response to roads, selection of vegetation cover near roads and open areas after ... : Funding provided by: German Federal Ministry of Transport and Digital Infrastructure (BMVI)*Crossref Funder Registry ID: Award Number: 19F2014B Funding provided by: Deutsche Wildtier Stiftung*Crossref Funder Registry ID: Award Number: Funding provided by: fct/mct*Crossref Funder Registry ID: Award Number: Funding provided by: EU Program Interreg IV 44*Crossref Funder Registry ID: Award Number: Funding provided by: Bavarian State Ministry of the Environment and Consumer Protection and the Bavarian Health and Food Safety*Crossref Funder Registry ID: Award Number: ...